1996
DOI: 10.1111/j.1348-0421.1996.tb01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tumor Necrosis Factor Alpha (TNFα) and Enhancement of HIV‐1 Replication in the J22HL60 Cell Line by Mycoplasma penetrans

Abstract: Mycoplasma penetrans isolated from clinical specimens of AIDS patients showed potent activity in tumor necrosis factor alpha (TNFα) production in THP‐1, U937 and J22HL60 cell lines, and in the enhancement of HIV‐1 replication in a dormantly‐infected J22HL60 cell line as compared with the activities of other mycoplasmas. Both activities were found in the methanol layer but not in the chloroform layer of the membrane extracted by the Bligh‐Dyer method. TNFα production was observed in the peritoneal macrophages f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…The detection of this species in the peripheral blood lymphocytes and urine of AIDS patients in a previous study suggested that it might have the ability to act as polyclonal activators of both T and B lymphocytes to stimulate the replication of HIV. It is thought to behave as a cofactor or immunomodulator in HIV-related diseases [39]. M. fermentans might be a systemic pathogen, causing fatal disease owing to the infection of the bone marrow in non-HIV-infected patients [40].…”
Section: Introductionmentioning
confidence: 99%
“…The detection of this species in the peripheral blood lymphocytes and urine of AIDS patients in a previous study suggested that it might have the ability to act as polyclonal activators of both T and B lymphocytes to stimulate the replication of HIV. It is thought to behave as a cofactor or immunomodulator in HIV-related diseases [39]. M. fermentans might be a systemic pathogen, causing fatal disease owing to the infection of the bone marrow in non-HIV-infected patients [40].…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate increased rates of HIV replication, probably through NF‐κB‐mediated regulation of the HIV LTR. TNF‐α induced by mycoplasma had been thought to induce NF‐κB and HIV replication; however, anti‐TNF‐α immunoglobulin failed to inhibit the enhancement of HIV replication by mycoplasma 18 . Although activation of NF‐κB has been implicated in the mycoplasma‐induced enhancement of HIV replication, the receptor(s) and the pathways of signal transduction via NF‐κB have not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Mycoplasmal products induce cytokines in cells from C3H/HeJ mice that respond poorly to LPS. Furthermore, cytokine induction is not inhibited by the LPS inhibitor polymyxin B (178,201,352,353). The results also show that the same Mycoplasma species may carry several cytokine-inducing molecules that are not necessarily identical to the mycoplasmal mitogenic elements.…”
Section: Proinflammatory Cytokinesmentioning
confidence: 99%
“…In addition, extraction of M. penetrans membranes with chloroform-methanol yielded, in the methanol layer, a carbohydrate-containing molecule capable of triggering TNF-␣ in murine cell lines (201). The activity of this molecule was inhibited by ConAsepharose but not by the LPS inhibitor polymyxin B. Appar-ently, M. penetrans lipoproteins (352) and the carbohydratecontaining factor (201) that induced cytokine differ from the mitogenic capsular glycolipid of M. penetrans (48), which was unable to elicit IL-1␤ or TNF-␣ in murine splenocytes and was inhibited by polymyxin B.…”
Section: Proinflammatory Cytokinesmentioning
confidence: 99%